The significance of follow-up in patients with dysmorphic features: a case from clinical practice - Mariya Levkova; Milena Stoyanova; Mari Hachmeriyan (Romanian Journal of Pediatrics)
Background. Kabuki syndrome is a rare disorder, that is characterized by typical facial dysmorphism, hypotonia, delay in intellectual and motor development. Case report. We present a case of a girl in whom polycystic left kidney was prenatally established. Born prematurely in 37 weeks by C section due to oligohydramnios. After birth, atresia of the anus with fistula, cysts in the left and reduced dimensions of the right kidney, were further established. A normal female karyotype was found and targeted sequencing analysis was conducted on a panel of 81 genes associated with renal abnormalities – no pathogenic variants were detected. The child was then followed up by its general practitioner. At the age of 2 years, she was again referred for genetic counseling, which revealed the following dysmorphic signs – long eye palpebral fissuras with ectropion of the lower eyelid, sparsed lateral eyebrows, depression of the nasal bridge, brachydactyly and others characteristic of Kabuki’s syndrome. The conducted molecular genetic analysis confirmed the clinical diagnosis – a likely pathogenic variant in the KMT2D gene was established. Conclusions. Certain pathognomonic facial may not present at birth and only appear after a few years. Therefore, monitoring of the evolution of dysmorphic traits is required.